Measuring language attitudes. The case of Trasianka in Belarus - Sender, Natallia (Linguistik Online, 2014)
stems from agriculture describing a 'mixed fodder of poor quality'. Language attitudes towards this variety have hardly been examined thus far. In a recent study based on the matched-guise technique, 227 Belarusian adolescents listened to and evaluated a female speaker reading the same text in Russian, Belarusian and Trasianka. When the speaker used Trasianka, she was given low ratings by test participants in matters of socio-structural issues such as profession and education. Regarding competence, the test participants assumed that the Trasianka speaker was less qualified, as shown by answers to a question on competencies in foreign languages. Finally, the test participants were more reluctant to accept the Trasianka speaker as a neighbor. With this responsiveness, they performed a bigger social distance. By these findings, there is ample reason to conclude that there are negative attitudes existing amongst today's population in Belarus regarding speakers of Trasianka.